The Looming Effects of Estrogen in Covid-19: A Rocky Rollout - Al-kuraishy, Hayder M.; Al-Gareeb, Ali I.; Faidah, Hani; Al-Maiahy, Thabat J.; Cruz-Martins, Natália; Batiha, Gaber El-Saber (Frontiers in Nutrition, 2021)
In face of the COVID-19 pandemic, an intensive number of studies have been performed in an intend to understand in a deeper way the mechanisms behind better or worse clinical outcomes. Epidemiologically, male subjects are 2.4 times more prone to severe acute respiratory syndrome-coronavirus type 2 (SARS-CoV-2) infection than females, with a similar scenario being also stated to the previous coronavirus diseases, namely SARS-CoV in 2003 and Middle East Respiratory Syndrome coronavirus diseases (MERS-CoV) in 2012. In addition, and despite aging is regarded as an independent risk factor for the severe form of the disease, even so, women protection is evident. In this way, it has been expected that sex hormones are the main determinant factors in gender differences, with the immunomodulatory effects of estrogen, progesterone and androgen in different viral infections, chiefly in COVID-19, being attracting more attentions as it might explain the case-fatality rate and male predisposition for COVID-19 severity. Here, we aim to provide an overview on the protective effects of estrogen in COVID-19.